Comparative Analysis of Trans Vaginal Ultrasound and Bishop Score For Successful Prediction of Induction of Labor in Term Primigravidas: Transvaginal ultrasound and Bishop score comparison - Anwar, Wajeeha; Mujahid, Naima; Usman, Fareeha; Bhatti, Shaista; Abideen, Zen Ul (Pakistan Journal of Health Sciences, 2024)
Successful prediction of labor induction outcomes in term primigravidas has significant implications for maternal and neonatal health. Objective: To compare trans vaginal ultrasound (TVS) and bishop score for successful prediction of induction of labor in term primigravidas. Methods: This cross sectional comparative study was carried out at Department of Gynecology and Obstetrics and Department of Radiology of Shahida Islam Medial Complex, Lodhran, Pakistan using non-probability purposive sampling technique. The duration of study was six months from October 2023 to March 2024. Booked primigravidas in-between 18 to 40 years at 37-40 gestational week having singleton pregnancy were included Each female underwent Bishop scoring and TVS ultrasound Results: From total 151 pregnant females mean age was 28.63 ± 8.12 years, mean gestational age was 40.24 ± 0.77 weeks, mean bishop score and mean cervical length measured by TVS was 6.95 ± 2.21 and 27.2 ± 3.98 mm respectively. 117 (77.48 %) females had positive Bishop Score, 106 (70.2 %) positive Cervical Length (>27 mm) and 90 (59.6 %) induction of labor. Diagnostic accuracy of Bishop Score was 65.9 % while for TVS ultrasound was 80.2 %. Significant difference of p<0.001 was reported in-between cervical length >27 mm on TVS and successful induction of labor. TVS showed higher sensitivity 89.7%, specificity 62.3%, positive predictive value 77% and negative predictive value 82.1% as compared to Bishop Score. Conclusions: The results of this study concluded that the assessment of cervical length on TVUS was more accurate than Bishop Score in predicting successful induction of labor in term primigravidas.